Atypical velogenic Newcastle disease in a commercial layer flock in Japan. (25th March 2015) - Umali, Dennis V.; Ito, Hiroshi; Shirota, Kazutoshi; Ito, Toshihiro; Katoh, Hiromitsu
Abstract : In 2002, a commercial layer flock in Japan was initially diagnosed as being infected with infectious bronchitis (IB) based on clinical signs, virus isolation, and serological analysis but was later found to be atypically infected with velogenic Newcastle disease virus (NDV) following molecular diagnosis. The flock had slightly decreased egg production and an increased occurrence of soft-shelled eggs without significant mortality. IB-like viruses were isolated, which caused dwarfing and curling in 12-day-old chicken embryos. Ten years after this case, retrospective genetic analyses showed that apart from IB virus (IBV), the flock was also infected with NDV. Mean death time (MDT), intracerebral pathogenicity index (ICPI), and deduced amino acid sequence of the cleavage site of the fusion (F)-protein gene revealed that the NDV isolate was velogenic ( 112 RRQKR 116 ). These results indicate that poultry clinicians should look out for atypical velogenic ND, especially in vaccinated commercial chicken flocks, which may harbor hidden NDV infection.